Participaç\~ao social e proteç\~ao de dados: Um estudo de caso sobre o Conselho Nacional de Proteç\~ao de Dados Pessoais e da Privacidade - Daniel Pitangueira de Avelino; Igor Ferraz da Fonseca; Jo\~ao Cláudio Basso Pompeu (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This text discusses the functioning of the recently created National Council for the Protection of Personal Data and Privacy (CNPD). This collegiate has typical characteristics of both advisory councils, with advisory attributions and subordination to a public authority, and public policy councils, such as the composition with a majority of non-governmental members. Brazilian legislation on data protection was more clearly influenced by European standards on the subject, compared to the models of the United States and the Organisation for Economic Cooperation and Development (OECD). Even so, the CNPD appears as a typically Brazilian construction in the governance structure of these public policies. Its creation and its first selective process for civil society representatives, described in this text, reveal the contradictions of the period and the specific challenges of this new collegiate.
Keywords: D73; H83; K24; 330; councils; data protection; data protection law